2020
DOI: 10.1177/1471301220905233
|View full text |Cite
|
Sign up to set email alerts
|

Features of primary care practice influence emergency care-seeking behaviors by caregivers of persons with dementia: A multiple-perspective qualitative study

Abstract: Background: Persons with dementia use emergency department services at rates greater than other older adults. Despite risks associated with emergency department use, persons with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…By incorporating these additional variables, such as cognitive status, caregiver burden, access to care, and social determinants of health, we can gain a deeper understanding of the factors contributing to recurrent ED visits among PLWD. For instance, work that we have previously done has identified that primary care providers do not have the resources to fully diagnose and treat PLWD, leading to their referral to the ED 4,10 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…By incorporating these additional variables, such as cognitive status, caregiver burden, access to care, and social determinants of health, we can gain a deeper understanding of the factors contributing to recurrent ED visits among PLWD. For instance, work that we have previously done has identified that primary care providers do not have the resources to fully diagnose and treat PLWD, leading to their referral to the ED 4,10 …”
Section: Figurementioning
confidence: 99%
“…For instance, work that we have previously done has identified that primary care providers do not have the resources to fully diagnose and treat PLWD, leading to their referral to the ED. 4,10 Future research must involve PLWD and their care partners as well. Qualitative research can provide insights into patient preferences, social and cultural factors influencing healthcare decisions, and the experiences of PLWD and their care partners as well as providing a deeper understanding of the barriers faced with ED transitions.…”
mentioning
confidence: 99%
“…Additionally, it's holistic approach to care can lead to a higher quality of life and improvement in the health and wellbeing of people living with dementia (Spenceley et al 2015), potentially extending time living in the place of their choice. However, with its complex physical, behavioural and psychosocial needs, dementia is poorly recognised, diagnosed and managed within general practice (Beck et al 2021). GP barriers to optimal dementia care include lack of knowledge and skills in the management of this disease and insufficient time to provide support to the person living with dementia and their carer (Heintz et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers report more emotional [28] and physical stress, more hours per week spent providing care, less time for themselves and other families, and had more work-related problems than caregivers of persons with noncognitive (physical) impairments [29]. In addition, emergency department use is associated with caregiver depression and care recipient functional, behavioral, and psychological symptoms [29,30]. Concerns about the needs of caregivers of persons with cognitive impairment, including dementia, have motivated the development of dementia care management programs [31,32], adult day centers, and community support services for people living with dementia and their caregivers.…”
Section: Introductionmentioning
confidence: 99%